Effect of hybrid SiC/TiO2 nanoparticles on tribological and mechanical performance of polymethylmethacrylate dental base material - Ahmed Rashed Ahmed; Abd Ali Hussein El (Zaštita Materijala)
Many researches dealt with PMMA dental base material and the development of its properties to reach a longer life span for implants and fillings. The current work pay attention to examine the loading amount of hybrid nanoparticles, SiC and TiO2, and find out how it affects the mechanical and tribological properties. Hybrid NPs were dispersed on PMMA resin with filler amount of 0.4%, 0.8%, 1.2%, 1.6%, and 2.0 wt.%, 50/50 between SiC and TiO2 NPs. The mechanical properties were evaluated by determining the hardness, Shore D, compressive strength, and modulus of elasticity. While the tribological performance was assessed via examining the COF, wear rate and scanning the worn surfaces using optical and SEM images. The results can be indicated that the PMMA resin exhibits a good reaction bonding with low loading amount of the hybrid NPs. Moreover, the high loading content had a negative effect on the mechanical and tribological properties. Subsequently, the loading content of 0.8 wt.% of SiC/TiO2 NPs indicates that it has the best performance comparing with the pure PMMA.